The bamboo sword - Preus, Margi (Amulet Books, 2016)
In Japan in 1853, at the time of U.S. Commodore Matthew Perry's visit to Japan, Yoshi, a young Japanese boy who dreams of becoming a samurai one day, learns about America from Majiro and has adventures with Jack, a young cabin boy aboard one of the U.S. ships. Includes historical notes and glossary.